Educação matemática e tecnologias: implicações do ensino na educação básica - Ferreira, Jorge Dias (2015)
This work in addition, to emphasizing the importance of the use of technology in contemporary times, particularly in the educational environment, aims to demonstrate how technology, in particular, the Graphmatica, software can contribute as a pedagogical element for educators and be a link that aggregates knowledge to learners. Didactic Engineering has been the methodological option for the realization of this survey. The implementation of the experiment has occurred in the field of adult and youth education and aimed to motivate students to understand the concepts related to the mathematical function according to the light of the theory of structuring milieu, favoring student's learning before the practical use of virtual materials.